New Insights into the Non-orthodox Two Component Rcs Phosphorelay System - Guo, Xiao-Peng; Sun, Yi-Cheng (Frontiers in Microbiology, 2017)
The Rcs phosphorelay system, a non-orthodox two-component regulatory system, integrates environmental signals, regulates gene expression and alters the physiological behavior of members of the Enterobacteriaceae family of Gram-negative bacteria. Recent studies of Rcs system focused on protein interactions, functions, and the evolution of Rcs system components and its auxiliary regulatory proteins. Herein we review the latest advances on the Rcs system proteins, and discuss the roles that the Rcs system plays in the environmental adaptation of various Enterobacteriaceae species.